Approximation by Penultimate Stable Laws - Laurens F.M. de Haan; Liang Peng; H. Iglesias Pereira (Tinbergen Institute, 1997)
In certain cases partial sums of i.i.d. random variables with finite variance are better approximated by asequence of stable distributions with indices alpha n -> 2 than by a normal distribution. We discusswhen this happens and how much the convergence rate can be improved by using penultimate approximations. Similar results are valid for other stable distributions.
Keywords: 330; Wahrscheinlichkeitsrechnung; Theorie